2022
DOI: 10.1021/acs.inorgchem.2c00911
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Metal–Organic Frameworks on Graphene Oxide Nanosheets and In Situ Conversion into a Nickel Hydroxide/Graphene Oxide Battery-Type Electrode

Abstract: Graphene oxide (GO) has been widely reported as a supercapacitor electrode. Especially, GO is usually utilized to composite with electrochemical active materials, such as transition-metal oxide/hydroxide/sulfide, due to its considerable conductivity and mechanical strength. However, the ideal design and treatment for compositing GO with active materials are still challenging. Herein, an Ni-metal−organic framework (MOF) was self-assembled on GO nanosheets via the solvothermal method and was subsequently etched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 60 publications
1
10
0
Order By: Relevance
“…Li et al [140] successfully produced Ni(OH) 2 -GO electrode materials using a two-step synthesis process. The numerous functional groups on GO nanosheets aid in the nucleation and growth of Ni-MOFs.…”
Section: Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [140] successfully produced Ni(OH) 2 -GO electrode materials using a two-step synthesis process. The numerous functional groups on GO nanosheets aid in the nucleation and growth of Ni-MOFs.…”
Section: Batteriesmentioning
confidence: 99%
“…The Ni(OH) 2 -GO electrode material exhibits exceptional stability (the capacity retention rate after 8000 cycles is 108%) and a high SC of 1007.5 C g −1 . The ASC device can operate with excellent stability at a power density of 393.29 W kg −1 and has an energy density of 65.22 Wh kg −1 when PPD-rGO is used as the negative electrode [140].…”
Section: Batteriesmentioning
confidence: 99%
“…To overcome these limitations, various strategies have been applied to oxide/hydroxide-based catalysts such as heterostructure engineering, doping, and anchoring single atoms. Through these approaches, the number of active sites where the reaction occurs increases, and the intrinsic conductivity of the catalysts can be improved [73][74][75][76][77][78][79][80][81][82]. The representative strategies to accomplish the advanced oxide/hydroxide-based catalysts are proposed in Figure 2.…”
Section: Strategies For Catalysts Design In Alkaline Mediamentioning
confidence: 99%
“…Fabricating a composite by incorporating highly conductive graphene nanosheets into Ni(OH) 2 materials is considered as the most effective strategy to enhance the intrinsic properties of Ni(OH) 2 . Li et al [ 52 ] reported a novel Ni(OH) 2 /rGO hybrid material, which not only exhibited a high specific capacity (1007.5 C g −1 at 0.5 A g −1 ), but also showed good life cycle stability (108% capacitance retention after 8000 cycles), revealing its good performance by incorporating rGO. Guo et al [ 53 ] prepared a Ni(OH) 2 /rGO hybrid electrode and found a high specific capacity (1388 C g −1 at 2 A g −1 ) and remarkable rate capability (785 C g −1 at 50 A g −1 ).…”
Section: Recent Advances In Materials For Hybrid Supercapacitorsmentioning
confidence: 99%